Wind energy development in Morocco: Evolution and impacts - Touria Haidi; Bouchra Cheddadi; Faissal El Mariami; Zineb El Idrissi; Ali Tarrak (Institute of Advanced Engineering and Science, 2021)
Over the past ten years, Morocco has been focusing on developing renewable energy, especially wind power. This new energy policy has enabled it to become, in 2017, the leading country in the Middle East and North Africa region and the second one in Africa in terms of installed wind power capacity. In 2019, Morocco moved for the first time from the status of electricity importer to that of electricity exporter, better yet green electricity. This paper provides a quantitative study of the demand, production and installed power capacity of electrical energy in Morocco over the past two decades. It mainly focuses on the evolution of installed wind power capacity and its share in the global energy mix during this period, as well as its future prospects by year 2030. This article presents a synthesis work based on an updated assessment of the carried-out wind projects and aims to assess the realization of Morocco’s national energy strategy which sets out to achieve 42% of renewable energy by 2020, and more specifically 14% of the overall energy mix being wind energy. It also aims to show the impact of wind energy integration in terms of energy autonomy, industrial integration and CO2 emissions reduction.